2014
DOI: 10.1002/eqe.2407
|View full text |Cite
|
Sign up to set email alerts
|

Approximate seismic risk assessment of building structures with explicit consideration of uncertainties

Abstract: SUMMARYAn approximate seismic risk assessment procedure for building structures, which involves pushover analysis that is performed utilizing a deterministic structural model and uncertainty analysis at the level of the equivalent SDOF model, is introduced. Such an approach is computationally significantly less demanding in comparison with procedures based on uncertainty analysis at the level of the entire structure, but still allows for explicit consideration of the effect of record-to-record variability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…Extensive studies have been performed in order to determine typical dispersions b NC of the capacity at failure for reinforced concrete (RC) building structures using S a (T) as the intensity measure (Kosič et al 2014(Kosič et al , 2016. The results of these studies showed that the values depend on the structural system and on the period of the structure T. However, in a simplified approach, it may be reasonable to assume b NC ¼ 0:5 as an appropriate estimate for RC building structures, with the exception of very stiff structures, where b NC is smaller.…”
Section: Summary Of the Pushover-based Risk Assessment (Pra) Methodsmentioning
confidence: 99%
“…Extensive studies have been performed in order to determine typical dispersions b NC of the capacity at failure for reinforced concrete (RC) building structures using S a (T) as the intensity measure (Kosič et al 2014(Kosič et al , 2016. The results of these studies showed that the values depend on the structural system and on the period of the structure T. However, in a simplified approach, it may be reasonable to assume b NC ¼ 0:5 as an appropriate estimate for RC building structures, with the exception of very stiff structures, where b NC is smaller.…”
Section: Summary Of the Pushover-based Risk Assessment (Pra) Methodsmentioning
confidence: 99%
“…Extensive studies have been performed in order to determine typical dispersions β NC of the capacity at failure for reinforced concrete (RC) building structures using S a (T) as the intensity measure (Kosič et al 2014(Kosič et al , 2016. The results of these studies showed that the values depend on the structural system and on the period of the structure T. However, in a simplified approach, it may be reasonable to assume β NC ¼ 0.5 as an appropriate estimate for RC building structures, with the exception of very stiff structures, where β NC is smaller.…”
Section: Summary Of the Pushover-based Risk Assessment (Pra) Methodsmentioning
confidence: 99%
“…Figure 10 shows the collapse fragility curves obtained from NLRH analyses and with SPO based approach. The latter curve is built considering PGAc,PO as median capacity and the logarithmic dispersion =0.5, as indicated in [33] for mid-rise old RC frame buildings. It can be noted that the fragility curve representation obtained starting from SPO analyses allows a fair approximation of NLRH-based curve.…”
Section: Original Buildingmentioning
confidence: 99%
“…In fact, as depicted in Figure 13, the median capacity for wrap1 increases from the original value of PGAc,PO =0.58g to PGAc,PO,wrap1=0.72g while for the wrap12 and wall configuration it increases up to PGAc,PO,wrap12=1.06g and PGAc,PO,wall=0.81g. Note that for the retrofit wall that adopts shear wall a logarithmic dispersion =0.63, as indicated in [33] for mid-rise coupled wall-frame buildings is adopted. Total repair costs are calculated for three building configurations and different earthquake intensities adopting the SPO approach and the procedure outlined in 2.2.…”
Section: Original Buildingmentioning
confidence: 99%